2021
DOI: 10.1111/1365-2664.13936
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of herbicide use on biodiversity, ecosystem services and timber production trade‐offs in forest plantations

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
(104 reference statements)
0
9
0
Order By: Relevance
“…Our results suggest that in intensively managed forest landscapes, stand-level activities that promote floral resources within the first several years following harvest are most likely to be effective in supporting wild bee communities. Recent work has shown that a moderate reduction in herbicide application in the initial years following harvest increases floral resource and pollinator species richness in early seral conifer plantations (Stokely et al, 2022) and may mitigate the undesirable impacts of ungulate herbivory and introduced plant species (Stokely et al, 2018(Stokely et al, , 2020. Associated revenue trade-offs may be low in some economic scenarios (Kormann et al, 2021) allowing "win-win" outcomes for timber production and biodiversity conservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that in intensively managed forest landscapes, stand-level activities that promote floral resources within the first several years following harvest are most likely to be effective in supporting wild bee communities. Recent work has shown that a moderate reduction in herbicide application in the initial years following harvest increases floral resource and pollinator species richness in early seral conifer plantations (Stokely et al, 2022) and may mitigate the undesirable impacts of ungulate herbivory and introduced plant species (Stokely et al, 2018(Stokely et al, , 2020. Associated revenue trade-offs may be low in some economic scenarios (Kormann et al, 2021) allowing "win-win" outcomes for timber production and biodiversity conservation.…”
Section: Discussionmentioning
confidence: 99%
“…In intensively managed plantations, these practices typically include (1) the removal of woody debris and residual vegetation, which increases the availability of light, nutrients, and soil moisture for crop trees; (2) planting nursery‐grown seedlings, which typically hastens early growth and increases the density of commercial tree species; and (3) herbicide application to suppress competing vegetation (Adams et al, 2005; Kormann et al, 2021). Such measures are implemented to maximize the growth of crop trees, yet simplify the composition and successional pathway of plant communities, limiting the longevity of the early seral period when animal‐pollinated plants are most dominant (Brockerhoff et al, 2008; Stephens & Wagner, 2007; Stokely et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the moist, high‐productivity forests of the PNW, herbicide is often used in tree plantations to reduce competing vegetation and increase tree growth and survival (Kormann et al, 2021). Kormann et al (2021) observed that increasing levels of aerial herbicide application resulted in fewer flowering plant species and individuals than the no‐herbicide control (Kormann et al, 2021; Stokely et al, 2021). Kormann et al (2021) also found that wild bee richness declined at similar rates as plant communities with changes in herbicide intensity, though abundance was not strongly impacted (Kormann et al, 2021; Stokely et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Pasture Integrating herbicide treatment into pyric herbivory may not lead to long term L. cuneata reduction at large scales relevant to rangeland management or conservation (i.e., > 100 m 2 ). Since chemical-based mitigation effort s often kill important nontarget species ( Fuhlendorf et al 2002 ;Stokely et al 2021 ), we utilized a lighter concentration herbicide mix (i.e., our conservation-oriented approach) for this study. It is possible that more aggressive herbicide mixes might be more effective at reducing L. cuneata .…”
Section: Lespedeza Cuneatamentioning
confidence: 99%
“…Rationales for rangeland management actions targeting invasive species reduction include increasing biodiversity and buffering against livestock productivity losses (Juliá et al 2007; Sheley et al 2011) (i.e., from the exclusion and reduction of palatable forage species by less palatable or toxic invaders such as Bromus tectorum or Centaurea stoebe [cheatgrass or spotted knapweed, respectively]). However, some of the more popular methods commonly employed to reduce invasive species (e.g., herbicide application) also carry negative consequences for biodiversity (Fuhlendorf, Engle, Arnold, and Bidwell 2002; Crone, Marler, and Pearson 2009; Rinella, Maxwell, Fay, Weaver, and Sheley 2009; Stokely et al 2021). Moreover, disturbance processes (e.g., fire and grazing) that are critical to biodiversity maintenance in many systems also favor invasion (Hobbs and Huenneke 1992; Lear et al 2020).…”
Section: Introductionmentioning
confidence: 99%